2014
DOI: 10.3389/fnins.2014.00363
|View full text |Cite
|
Sign up to set email alerts
|

Choroid plexus in developmental and evolutionary perspective

Abstract: The blood-cerebrospinal fluid boundary is present at the level of epithelial cells of the choroid plexus. As one of the sources of the cerebrospinal fluid (CSF), the choroid plexus (CP) plays an important role during brain development and function. Its formation has been studied largely in mammalian species. Lately, progress in other model animals, in particular the zebrafish, has brought a deeper understanding of CP formation, due in part to the ability to observe CP development in vivo. At the same time, adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 121 publications
(162 reference statements)
1
44
0
Order By: Relevance
“…Using claudin-2, a marker of adult epithelium in the CP (Kratzer et al 2012), we did not observe co-localization with GAS1 in neither the LV nor in the 3V confirming at least by exclusion that GAS1 is expressed in the stroma of the CP. The stroma of the CP is mainly composed by endothelial cells and to a lesser extent by a wide variety of cells including: pericytes, fibroblasts, telocytes, stem cells, dendritic cells, macrophages, leukocytes, Kolmer cells, and in some cases T-cells (Strazielle and Ghersi-Egea 2000;Emerich et al 2005b;Bill and Korzh 2014). We then examined the expression of GAS1 in endothelial cells, because they are the most common cells in the stroma but also because there is an in vitro report indicating that endothelial cells express GAS1 (Spagnuolo et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Using claudin-2, a marker of adult epithelium in the CP (Kratzer et al 2012), we did not observe co-localization with GAS1 in neither the LV nor in the 3V confirming at least by exclusion that GAS1 is expressed in the stroma of the CP. The stroma of the CP is mainly composed by endothelial cells and to a lesser extent by a wide variety of cells including: pericytes, fibroblasts, telocytes, stem cells, dendritic cells, macrophages, leukocytes, Kolmer cells, and in some cases T-cells (Strazielle and Ghersi-Egea 2000;Emerich et al 2005b;Bill and Korzh 2014). We then examined the expression of GAS1 in endothelial cells, because they are the most common cells in the stroma but also because there is an in vitro report indicating that endothelial cells express GAS1 (Spagnuolo et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…To compare the network to previously published results, we used a configuration analogous to the setup presented in the work of Bill and Legenstein 40 , who used a model of memristive elements in an unsupervised Winner-take-all network to learn digit prototypes for digits zero to four. A downscaled network of this kind has been partially verified in hardware recently 33 .…”
Section: System-level Behavioral Simulationsmentioning
confidence: 99%
“…Conversely, the cycle-to-cycle variability (e.g., in groups G1 and G2) can be managed by using feedback control to set the desired state to a well-defined value 35 , which requires a large overhead control circuit, or it can be exploited as a means to implement stochastic learning in spiking neural networks 25,26,[36][37][38][39] . Indeed, it has been shown that employing binary synapses, variability and randomness in their switching threshold in spiking neural networks greatly improves the convergence of the network and provides a form of regularization which substantially improves the network generalization performance 26,40,41 . In the case of neural networks with low resolution synapses, it has been shown that a randomized gradient descent method significantly outperforms naive deterministic rounding methods 42 .…”
mentioning
confidence: 99%
“…A second barrier is formed between blood and cerebrospinal fluid and is sustained by tight junctions between epithelial cells in the choroid plexus (Engelhardt & Sorokin, 2009). Choroid plexus are evolutionarily conserved, highly vascularized structures that protrude into the brain ventricles as well as the subarachnoid space (Bill & Korzh, 2014). Choroid plexus are made of epithelial cells specified from the neuroectoderm as early as E10.5 in the mouse embryo (Liddelow, 2015).…”
Section: Functions Of Perivascular Meningeal and Choroidal Macrophagesmentioning
confidence: 99%